Bridging Culture and Mathematics: Exploring Teachers’ Needs for Culturally Relevant Digital Resources in Primary Schools - Rahayu Condro Murti; Yeni Rakhmawati; Unik Ambarwati; Tiara Harsono; Salman Rashid (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to evaluate the feasibility and user acceptance of the Matematika Berbudaya e-book as a culturally responsive digital resource for primary mathematics learning in the Special Region of Yogyakarta, Indonesia. This study used a design and development research method with a field trial evaluation to assess the feasibility, acceptability, and perceived pedagogical value. A field trial involved 10 teachers and school leaders who completed a 26-item five-point questionnaire with an open-ended comment, and 89 students who completed a 20-item four-point questionnaire after using the e-book. Descriptive statistics were used to summarize item-level means and response distributions, and internal consistency was examined with Cronbach’s alpha. Teachers reported strong endorsement of value integration and meaningful learning (M = 4.80 and 4.70), contextual and cultural integration (highest M = 4.90), and perceived usefulness and access (M from 4.50 to 4.60). Students also responded positively, with an overall mean of 3.3494 and responses concentrated in the upper categories (scores 3 and 4). The combined results indicate that the e-book is perceived as culturally meaningful, practically usable, and supportive of engaging learning experiences. These findings provide an empirical basis for refining instructional wording, layout cues, and navigation, and for informing the development of culturally grounded digital materials that align with Kurikulum Merdeka and principles of culturally responsive teaching.